Organizational design: the case of SARS-CoV-2 vaccination in a healthcare centre - Catalano, S.; Ossino, A. M.; Tribastone, S.; Cantaro, S. P. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Only recently Anti-Covid-19 strategies have been applied through specific  vaccines, that are a decisive support to modify the evolution of the disease and to reduce the contagion curve. Along vaccination campaigns, the necessity to guarantee rapidity and effectiveness is a critical challenge for all health organizations; their operative capability is applied to carry out govern plans, to ensure safety of the procedures, to adopt good clinical practices, to help with adhesion to vaccine administration and to monitor adverse effects.Study design. The “Centro Clinico Morgagni” is a private accredited diagnosis and treatment Centre with high specialty departments and several hospital beds. The challenge for its administration was to complete the vaccination of all the staff, so a COVID19 crisis unit was established to assure the control of all activities in the center throughout the pandemic. The goal was to complete the vaccination plan following the guidelines with no risks or harm.Methods. An original organizational model, based on different planning methodologies was developed, its task was to define a standard procedure and to give operational instructions based on ISO 9001 for monitoring the entire vaccination process. Also, the model had to define every responsibility role and it had to follow Joint Commission International’s methodologies as far as error barriers, drug conservation risks, drug transport and drug administration were concerned.Furthermore, in agreement with the HACCP system, critical control points were highlighted during all the process. The results have been processed in the form of quick references and illustrative panels based on relevant process aspects, which were given to the staff involved in the operations as reference tools for prompt consultation.Results. The vaccination operations at the Centro Clinico Morgagni took place quickly in only four days: 800 staff units were vaccinated – first and second doses with Covid19 mRNA BNT162b2 (Cominraty) - in three different vaccination centers without highlighting significant events that did not comply with the guidelines, nor deviations from the established goals. More precisely, starting from 277 bottles corresponding to six doses each, only 0.2% was wasted, while ADR monitoring reported a prevalence of adverse effects in females (78%) compared to males (22%). Adhesion Organizational design – SARS-CoV-2 vaccination centre for vaccination of qualified personnel, thanks to the activities of the Medical College set up for this purpose, reached 100% of the candidate staff through repeated personalized interviews with only one opposition, compared to the 30 communicated at the beginning.Conclusions. It was necessary to ensure the efficiency of the entire process and the model was tested positively. This model can also provide a security control of all the vaccinated personnel; its schematization allows an easy application and flexibility, thus making it an organizational tool that could be reproduced and transferred to other contexts.